Application of two dimensional thin layer chromatography pattern comparison for fingerprinting the active compaounds in the leaves of Vitex Trifolia linn processing anti-tracheospasmolytic activity - Khatib, Alfi; Hoek, Arie C.; Jinap, Selamat; Sarker, Md. Zaidul Islam; Jaswir, Irwandi; Verpoorte, Robert (Taylor & Francis Group, 2010)
We have developed one approach to fingerprint and estimate the active compounds in the leaves of Vitex trifolia Linn possessing anti-tracheospasmolytic assay using two-dimensional TLC pattern comparison. Based on the two-dimensional TLC pattern and the activity of the centrifugal partition chromatography fractions, we concluded that the semi polar compounds were responsible for anti-tracheospasmolytic activity. The best non-polar=semi polar mobile phases for the two-dimensional TLC using silica gel as the stationary phase were chloroform=methanol (9=1) as the first mobile phase and ethyl cetate=chloroform=methanol (28=28=44) as the second mobile phase.